New statistical Binary Random Test - Taha, Imad; Hasan, Luay (Al Rafidain University College, 2006)
Binary streams can be tested using standard tests. the efficiency of some tests is not remarkable big, because they do not examine some stream features, which are important to be verified (for example, mono-bit test satisfied every stream that consists of approximate one half zeros(i.e, ones), no matter if all of them are consecutive or alternate), and so several tests are to be combined. In our proposed test, distribution of frequencies of blocks and gaps are determined and for given number of blocks and gaps expected distribution of frequencies is expected. X2 is calculated and it is checked whether the probability of it is above the threshold of significance. In the same way both distributions (blocks and gaps) are evaluated.